Synthesis of alternan-stabilized zinc nanoparticles: morphological, thermal, antioxidant and antimicrobial characterization - Yucel, Nur; Ispirli, Humeyra; Mercan, Emin; Erdogan, Ummugulsum; Dertli, Enes (TAYLOR & FRANCIS INC, 2021)
This study aimed to synthesize zinc nanoparticles with antimicrobial and antioxidant activities using alternan (ZnNPs-Alt) produced byLactobacillus reuteriE81 as the stabilizing agent. For the characterization of the ZnNPs-Alt, UV-vis spectroscopy, SEM, TEM and EDX analysis, XRD, FTIR and DSC analysis were applied. The functional role of ZnNPs-Alt was tested by determination of their antioxidant activities by DPPH and CUPRAC methodologies and their antibacterial and antifungal activities. Results of this study demonstrated that alternan was utilized as a successful stabilizer to produce crystalline, thermally stabile ZnNPs-Alt with a particle size of similar to 100 nm. Importantly, strong antioxidant and antimicrobial activities were observed for ZnNPs-Alt in a concentration dependent manner. These findings confirmed the role of alternan as a stabilizing agent for the production of ZnNPs-Alt with functional roles.
Keywords: Alternan; antimicrobial; antioxidant activity; morphology; zinc nanoparticles; OXIDE NANOPARTICLES; ANTIFUNGAL ACTIVITY; LEAF EXTRACT; ZNO; ANTIBACTERIAL; GLUCAN; GREEN; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology